Zero-Valent Iron Sand Filtration Can Reduce Human and Plant Pathogenic Bacteria While Increasing Plant Growth Promoting Bacteria in Reclaimed Water - Kulkarni, Prachi; Olson, Nathan D.; Bui, Anthony Q.; Bradshaw, Rhodel N.; Del Collo, Laura P.; Hittle, Lauren E.; Handy, Eric T.; Paulson, Joseph N.; Ghurye, Jay; Nasko, Daniel J.; East, Cheryl; Kessel, Jo Ann Van; et al. (Frontiers in Environmental Science, 2020)
The increasing use of reclaimed water for irrigation in areas lacking access to advanced wastewater treatment and reclaimed water distribution systems calls for an examination of irrigation-site-based treatment technologies that can improve the quality of this alternative water source. To address this need, we investigated the impact of zero-valent iron (ZVI)-sand filtration on the bacterial community structure and functional potential of conventionally treated reclaimed water utilized in downstream applications. Over a two-month period, reclaimed water was collected from a tertiary wastewater treatment plant in the Mid-Atlantic, U.S. and trucked to our greenhouse facility. The water was stored in rain barrels and then filtered through one ZVI-sand filter every five days. Filtrate was then subjected to enumeration, phylotyping, shiga toxin screening and antimicrobial susceptibility testing of Escherichia coli. Aliquots of filtrate were also DNA extracted, and purified DNA was subjected to 16S rRNA gene sequencing and metagenomic shotgun sequencing. The genera Dechloromonas, Desulfotomaculum, Leptonema and Thermomonas, which contain denitrifying and sulfate reducing species, commonly used in bioremediation, and known to increase the inherent reactivity of ZVI, were significantly more relatively abundant in ZVI-sand filtered reclaimed water compared to reclaimed water. The concentration of E. coli in ZVI-sand filtered reclaimed water was significantly lower compared to that of reclaimed water, and cefoxitin- and tetracycline-resistant E. coli were undetectable after ZVI-sand filtration. ZVI-sand filtration reduced the occurrence of human as well as plant pathogenic genera (Aeromonas, Mycobacterium, Shewanella, Acidovorax, Agrobacterium, Clavibacter) but increased the proportion of Azospira, a nitrogen fixing bacterial genera, in the microbial community. Our exploratory functional analysis showed a modest non-significant increase in the proportion of open reading frames for genes associated with iron uptake, oxidative stress, as well as defense and repair mechanisms after ZVI-sand filtration. These data indicate an iron rich environment in the filter causing an oxidative stress response by the bacterial community present in the reclaimed water. Our findings demonstrate that ZVI-sand filtration effectively filters conventionally treated reclaimed water. Longer-term, field-based studies are needed to evaluate the effectiveness of the filter in agricultural settings and inform the development of future agricultural water reuse regulations.